Effect of medication timing on anticoagulation stability in users of warfarin (the INRange RCT): study protocol for a randomized controlled trial. Issue 1 (December 2016) - Heran, Balraj; Allan, G.; Green, Lee; Korownyk, Christina; Kolber, Michael; Olivier, Nicole; Flesher, Mary; Garrison, Scott
Abstract Background Warfarin is an oral anticoagulant medication that disrupts the liver's production of clotting factors. While this medication is highly effective for the prevention of thromboembolic events, it also has a narrow therapeutic range and a vulnerability to interactions with other drugs and vitamin K-containing foods. Warfarin is commonly ingested at dinnertime, the same time of day that dietary vitamin K consumption (found largely in green leafy vegetables) is most variable. While the long half-life of warfarin might make this irrelevant, the ultra short half-life of vitamin K and the possibility of a hepatic first-pass effect for warfarin make it worth evaluating whether morning ingestion of warfarin, when vitamin K levels are consistently low, leads to greater stability of its anticoagulant effect. An examination of the timing of administration on the effectiveness of warfarin has never before been conducted. Methods/design This is a 7-month Prospective Randomized Open Blinded End-point (PROBE) study in which established evening warfarin users (primary care managed Canadian outpatients in the provinces of British Columbia and Alberta) will be randomized to either switch to morning ingestion of warfarin (the intervention) or to continue with evening use (the control). The primary outcome is the percent change in the proportion of time spent outside the therapeutic range of the international normalized ratio (INR) blood test. Secondary outcomes include change in proportion of time spent within the therapeutic INR range (TTR), percentage of patients with TTR >75 %, percentage of patients with TTR <60 %, and major warfarin-related cardiovascular events (including all-cause mortality, hospitalization for stroke, hospitalization for GI bleeding, and deep venous thrombosis/pulmonary embolism). We will also compare whether day-to-day variability in the consumption of high vitamin K-containing foods at baseline affects the baseline TTR in this cohort of evening warfarin users. Discussion This study addresses whether the timing of warfarin ingestion influences the stability of its anticoagulant effect. Should morning ingestion prove superior, the safety and effectiveness of this medication, and hence the prevention of stroke, pulmonary embolus, and major hemorrhage, could potentially be improved with no added cost or inconvenience to the patient. Trial registration ClinicalTrials.gov:NCT02376803 . Registered on 25 February 2015.